2005
DOI: 10.1016/s0140-6736(05)66416-1
|View full text |Cite
|
Sign up to set email alerts
|

Supervised versus unsupervised intake of six-dose artemether-lumefantrine for treatment of acute, uncomplicated Plasmodium falciparum malaria in Mbarara, Uganda: a randomised trial

Abstract: CitationSupervised versus unsupervised intake of six-dose artemether-lumefantrine for treatment of acute, uncomplicated Plasmodium falciparum malaria in Mbarara, Uganda: a randomised trial., 365 (9469 Articles IntroductionWith an estimated 500 million individuals affected every year, malaria is a leading cause of morbidity and mortality in sub-Saharan Africa along with HIV/AIDS. 1Of the 1 million deaths caused by malaria worldwide, about 90% occur in African children, a situation compounded by the emergence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
169
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(192 citation statements)
references
References 31 publications
22
169
1
Order By: Relevance
“…The high reported adherence found in this study can be explained by the availability of ALu in pre-packaged packets with pictorial instructions, which have been reported to improve caretakers' understanding of the schedule administration of the drug 30 and hence they are more likely to follow the provider's advice. 12,22,31 Studies conducted when CQ resistance was high reported low adherence levels, 10,11 thus the highly efficacious ALu used in the present study might also explain the high reported level of adherence to treatment.…”
Section: Discussionmentioning
confidence: 71%
“…The high reported adherence found in this study can be explained by the availability of ALu in pre-packaged packets with pictorial instructions, which have been reported to improve caretakers' understanding of the schedule administration of the drug 30 and hence they are more likely to follow the provider's advice. 12,22,31 Studies conducted when CQ resistance was high reported low adherence levels, 10,11 thus the highly efficacious ALu used in the present study might also explain the high reported level of adherence to treatment.…”
Section: Discussionmentioning
confidence: 71%
“…As a follow-up to confirm compliance to the evening doses, patients were asked on each follow-up day to confirm that the correct doses were taken at the right time and that vomiting did not occur after drug intake. Although the issue of non-compliance is a real concern, a similar study conducted in Ethiopia in 2004 to assess the efficacy of AL for the treatment of uncomplicated falciparum malaria, where the evening doses of AL were not supervised, reported a 99% rate of treatment success 19 Another study conducted in Uganda 20 Contrary to the high level of efficacy of AL for the treatment of P. falciparum, its efficacy for the treatment of P. vivax does not seem as high. In a study conducted in Thailand 21 comparing the efficacy of CQ and AL combined with a 14-day course of primaquine, full treatment success was achieved in the CQ treatment group, whereas the treatment success with AL was slightly lower at 97.4%.…”
Section: Discussionmentioning
confidence: 99%
“…10 In African children, effi cacy of artemether-lumefantrine at day 28 after treatment is consistently more than 90%, [11][12][13][14][15][16] even with unsupervised administration. 17,18 However, many young children cannot swallow whole tablets, and the bitter taste of the crushed commercial tablet added to water could compromise tolerability. Also, crushing tablets is an ineffi cient procedure, which could result in loss of drug and reduced dose ingested.…”
Section: Introductionmentioning
confidence: 99%